Geotourism Prospect in and around Dubrajpur, Birbhum, West Bengal, India - Saha, Bikas (The Nucleus, 2023)
In this era, it is not a luxury to see new places but a natural urge of the people, making tourism a huge industry. Tourists used to travel and tour for religious, cultural, educational, employment, business, health and adventure purposes. Geomorphologically, the Indian subcontinent is a land of great diversity. It is famous for its grand scenery. Almost all the geomorphic landscapes of the earth are present in this subcontinent. The Himalaya came up with blessings for India and India’s grand scenery in the subcontinent. Geotourism is a new form of tourism that is based on geomorphology, geology and also on different geological environments. Geotourism offers a new form of sustainable tourism that is more holistic than previous niche forms of tourism. There are some incredible rocks/rock formations across the Indian Sub-continent which can be the foundation of a geotourism site. The balancing rock forms a startling type, where one or more rocks are balancing on each other. Some of the finest examples are the ‘Balancing rock’ of Jabalpur, the balancing rock of Mahabalipuram, Tamil Nadu which is distinguished as ‘Krishna’s Butter Ball’, and the balancing rocks of ‘Mama-Bhagne Pahar’ in Dubrajpur. Among these three amazing spots, the first two is already well known to tourists, however, Mama-Bhagne pahar also offers a famous geomorphosite that has potential from geotourism perspective. However, there are some problems related to anthropogenic interventions that have to overcome to make it a famous geotourism site. Therefore, in the present study, an attempt has been made to formulate geoconservation and geotourism development strategies for the concerned geomorphosite that will protect the site from human activities and promote local tourism in a sustainable way. Moreover, Dubrajpur is located in the approachable vicinity of some popular and famous tourist spots of Birbhum district like Tarapith, Nalhati, Pathar Chapuri, Siuri, Amkhoi, Bolpur, Santiniketan and the very famous Bakreswar.